Pantoea agglomerans septicemia in a preterm neonate: A case report (Indian Journal of Case Reports, 2026)
Neonatal sepsis remains a significant cause of morbidity and mortality, particularly in preterm infants. We present a case of late-onset sepsis caused by atypical pathogen Pantoea agglomerans in a 27-day-old preterm male neonate, following traditional head shaving and application of an herbal poultice. Blood culture using an automated system flagged positive within 24 h, and identification with VITEK 2 confirmed P. agglomerans. The isolate demonstrated broad susceptibility to beta-lactams and carbapenems, intermediate susceptibility to aminoglycosides, and resistance to ciprofloxacin. Empiric therapy was modified based on susceptibility results, resulting in clinical recovery. This case emphasizes the significance of detailed exposure history and recognition of unusual pathogens with rapid microbial diagnostics in neonatal sepsis. Awareness and consideration of traditional cultural practices as potential infection sources may facilitate earlier diagnosis and targeted therapy, improving outcomes in high-risk neonates.